2012
DOI: 10.1038/oby.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

From Metabolic Normality to Cardiometabolic Risk Factors in Subjects With Obesity

Abstract: The aim of the study was to evaluate the 3 years incidence of cardiometabolic risk factors, such as impaired fasting glucose, reduced high‐density lipoprotein (HDL)‐cholesterol, increased plasma triglycerides or blood pressure as well as impaired glucose tolerance in overweight or obese (ow/ob) and normal body weight (nbw) subjects metabolically normal at baseline. Subjects from the Relationship between Insulin Sensitivity and Cardiovascular Disease (RISC) study were analyzed. We analyzed 284 nbw and 152 ow/ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…It is possible that middle-aged individuals who were overweight and obese for many years without developing any metabolic abnormalities confer a lower risk for incident CAD as compared to young adults in whom obesity sustained for a shorter interval. In support, Bobbioni-Harsch et al (25) and Bell et al (26) have used similar metabolic definitions to ours and showed that the MH obese are at risk for future metabolic abnormalities even after two decades from initial assessment. Moreover, BMI at late adolescence (27), even independent from that at young adulthood (1), has been shown to affect future adjusted CAD risk, pointing the critical role of obesity at young ages in the development of atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is possible that middle-aged individuals who were overweight and obese for many years without developing any metabolic abnormalities confer a lower risk for incident CAD as compared to young adults in whom obesity sustained for a shorter interval. In support, Bobbioni-Harsch et al (25) and Bell et al (26) have used similar metabolic definitions to ours and showed that the MH obese are at risk for future metabolic abnormalities even after two decades from initial assessment. Moreover, BMI at late adolescence (27), even independent from that at young adulthood (1), has been shown to affect future adjusted CAD risk, pointing the critical role of obesity at young ages in the development of atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 80%
“…To address this question, we studied the incidence of CAD among participants of the Metabolic, Lifestyle and Nutrition Assessment in Young Adults (MELANY) cohort. All of the men in the Israel Defense Forces (IDF) aged 25 and older have been metabolically characterized and followed in this large ongoing study. Data from this cohort were analyzed to compare the incidence of CAD among overweight and obese individuals with or without the various components of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Bobbioni-Harsch et al also found that weight gain was significantly associated with the development of cardiometabolic risk factors. 24 Similarly; Alpsoy et al and Ozcetin et al established that overweight and obese children were also potentially at risk of early atherosclerosis. 25,26 The INTERHEART study identified obesity as an important risk factor for myocardial infarction which was expressed with four different measurements: BMI, WHR, WC and HC.…”
Section: Discussionmentioning
confidence: 99%
“…In normal weight and obese adults [28] and after euglycemic-hyperinsulinemic clamp there was not greater cardiometabolic risk for them insofar as they showed normal insulin sensitivity. This together with the better known experiences about insulin resistance and its associated risks for CVD in adults [29] or pediatric ages [30] should lead to a more efficient search for fasting insulin levels or better for the whole metabolic syndrome factors in all of the overweight people with elevated blood pressure [31], which would imply an earlier preventive intervention.…”
Section: Discussionmentioning
confidence: 99%